PENGARUH EFISIENSI DAN EFEKTIVITAS PENERIMAAN PAJAK DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PAD DENGAN JUMLAH PENDUDUK SEBAGAI VARIABEL MODERASI PADA PEMERINTAH KOTA PROVINSI JAWA TENGAH - Sang Ayu Kompiang Puspita Wulandari; Abdul Rohman (Diponegoro Journal of Accounting, 2025)
The component of increasing Regional Original Revenue (PAD), namely local taxes and retribution, is very important in the sustainability of regional development and progress to harmonize decentralization. The focus of this study is to obtain empirical evidence on the influence of Local Taxes Efficiency and Local Retribution, Local Taxes Effectiveness and Local Retribution on the increase of city government PAD in Central Java Province. Based on the limitations of previous research, this study added the population as a moderation variable to test the relationship between independent and dependent variables.This research used secondary data obtained from the financial statements of city governments in Central Java for the 2018-2023 period so that 36 research samples can be obtained. The analysis methods used were quantitative descriptive methods and multiple linear regression analysis with special analysis of the influence of population as a moderation variable.The results of the research show that the efficiency of local taxes has a positive and significant effect on increasing PAD. Meanwhile, the efficiency of local retribution revenue and the effectiveness of tax revenue and local retribution do not have a significant influence on the increase in PAD. On the other hand, population size has not been proven to moderate this influence, where cities with large tax and local retribution bases do not automatically increase PAD as a result of the population in each of these cities.